2021
DOI: 10.1186/s43170-021-00025-y
|View full text |Cite
|
Sign up to set email alerts
|

Effect of rhizobial inoculants on yield and yield components of faba bean (Vicia fabae L.) on vertisol of Wereillu District, South Wollo, Ethiopia

Abstract: Background Nitrogen fixation by legumes like faba bean is a cheap way of fixing atmospheric nitrogen to plant available form. However, the inoculation of grain legumes with rhizobium bacteria are poorly researched in Amhara Region of Ethiopia. Methods Thus, a study to examine the effects of rhizobium leguminosarum (var vicae) strains on nodulation, growth, and yield of faba bean was conducted in Wereillu district of Amhara Region, Ethiopia during t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 17 publications
3
9
0
Order By: Relevance
“…[27] reported that inoculation of the Rhizobium strain with faba bean seeds produced highest nodules. Likewise, the results of [26] and [28] confirmed that inoculation of Rhizobium strains in faba beans significantly increased the number of nodules. Desta et al [23] also reported that inoculation of rhizobia from faba bean significantly increases the number of nodules/plant.…”
Section: Effect Of Inoculation On the Number Of Nodulessupporting
confidence: 56%
See 1 more Smart Citation
“…[27] reported that inoculation of the Rhizobium strain with faba bean seeds produced highest nodules. Likewise, the results of [26] and [28] confirmed that inoculation of Rhizobium strains in faba beans significantly increased the number of nodules. Desta et al [23] also reported that inoculation of rhizobia from faba bean significantly increases the number of nodules/plant.…”
Section: Effect Of Inoculation On the Number Of Nodulessupporting
confidence: 56%
“…This result is consistent with the finding of [25] who reported that inoculation of bacterial rhizobia strains resulted in significant above ground biomass in faba beans. Gedamu et al also showed that inoculation of rhizobia strains significantly affected the weight of faba bean biomass compared to without treatment inoculate [26]. The difference in biomass yield obtained from inoculation of faba bean is that Rhizobium strains could be due to the additional supply of nitrogen through the remarkable biological nitrogen [26], the rhizobia strain alone could significantly increase the number of pods/plants.…”
Section: Effect Of Inoculation On Above Ground Biomassmentioning
confidence: 99%
“…These findings are similar to previous studies ( Gomoung et al., 2017 ) reporting that inoculation of BGN with rhizobial strains induced a considerable increase in plant length, fresh weight, and dry weight. Additionally, it was noted ( Gedamu et al., 2021 ) that rhizobial inoculants enhance plant dry weight. It was observed that inoculating plants with Bradyrhizobium strain CB756 and (NC-92) peat-based commercial inoculants led to considerably increased dry matter yields in South Africa and northern Punjab, Pakistan, compared to un-inoculated controls ( Latif et al., 2014 ; Chidebe et al., 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Te elevation ranges are also based at 1428-2752 m above sea level, with a mean annual rainfall of 1130 mm, while the mean minimum and maximum temperatures of the district are 9 and 21 °C, respectively. Te main types of crops grown are wheat, fenugreek, barley, and tef [37]. Te main economic activity in the study area was agriculture, which depends on rainfall farming.…”
Section: Methodsmentioning
confidence: 99%